2012
DOI: 10.5535/arm.2012.36.5.596
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electric Cortical Stimulation after Focal Traumatic Brain Injury in Rats

Abstract: ObjectiveTo evaluate the effects of electric cortical stimulation in the experimentally induced focal traumatic brain injury (TBI) rat model on motor recovery and plasticity of the injured brain.MethodTwenty male Sprague-Dawley rats were pre-trained on a single pellet reaching task (SPRT) and on a Rotarod task (RRT) for 14 days. Then, the TBI model was induced by a weight drop device (40 g in weight, 25 cm in height) on the dominant motor cortex, and the electrode was implanted over the perilesional cortical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
1
20
0
1
Order By: Relevance
“…29,46,55 Advantages of the experimental model of hemispherotomy proposed here include the opportunity to study the morphology and functional characteristics of novel neural connections arising from adaptive neuroplasticity in the disconnected brain through the emergence of new subcortical projections and their inputs to the ventral horn of the spinal cord. In addition, we should highlight the functional role played by neuronal activity in the basal nuclei, brainstem-descending reticular-spinal projections, and cerebellum in recovering animals; neuronal and myelin plasticity; 11 electrical stimulation; 27,54 and neurophysiological mechanisms 42 previously suggested by several researchers. 34,43,46,49 The current model of hemispherotomy also enables the development of new rehabilitation strategies in rodents undergoing experimental hemispherotomy for the improvement of postsurgical recovery after hemispheric injuries, and it allows us to describe the neurological bases of this surgical therapeutic intervention in children with pharmacologically refractory epilepsy.…”
Section: Figmentioning
confidence: 99%
“…29,46,55 Advantages of the experimental model of hemispherotomy proposed here include the opportunity to study the morphology and functional characteristics of novel neural connections arising from adaptive neuroplasticity in the disconnected brain through the emergence of new subcortical projections and their inputs to the ventral horn of the spinal cord. In addition, we should highlight the functional role played by neuronal activity in the basal nuclei, brainstem-descending reticular-spinal projections, and cerebellum in recovering animals; neuronal and myelin plasticity; 11 electrical stimulation; 27,54 and neurophysiological mechanisms 42 previously suggested by several researchers. 34,43,46,49 The current model of hemispherotomy also enables the development of new rehabilitation strategies in rodents undergoing experimental hemispherotomy for the improvement of postsurgical recovery after hemispheric injuries, and it allows us to describe the neurological bases of this surgical therapeutic intervention in children with pharmacologically refractory epilepsy.…”
Section: Figmentioning
confidence: 99%
“…Direct cortical stimulation can induce plasticity in somatosensory areas of macaque monkeys, and cortical stimulation enhances functional recovery and cortical plasticity in the setting of neural injury, such as stroke in squirrel monkeys. 69,119,144,162 Stimulation during rehabilitation following motor cortex injury improves motor function in both rats and primates. 119,162 In animal experiments using intracortical microstimulation, cortical surface electrodes stimulating the motor cortex at subthreshold levels during rehabilitation after focal motor cortex ischemia can increase forelimb function.…”
Section: Cortical Stimulationmentioning
confidence: 99%
“…69,119,144,162 Stimulation during rehabilitation following motor cortex injury improves motor function in both rats and primates. 119,162 In animal experiments using intracortical microstimulation, cortical surface electrodes stimulating the motor cortex at subthreshold levels during rehabilitation after focal motor cortex ischemia can increase forelimb function. 69,119 This functional improvement following motor cortex infarction is induced by restoration of movement representation in peri-infarct areas, as well as the emergence of novel representations.…”
Section: Cortical Stimulationmentioning
confidence: 99%
“…New therapeutic strategies are needed for treatment of neurological functional deficits followingtraumatic or ischemic brain injury. Neuromodulation approach has been employed to treat stroke and TBI in animal models [7][8][9][10][11] and clinical studies [12][13][14], with preliminary data showing that neurostimulation may lead to functional improvement in the setting of brain injuries. A few animal studies in non-human primates have observed thatcortical stimulationenhances functional recovery and cortical plasticity after neural injury induced by stroke [7][8][9].…”
Section: Neuromodulation For Brain Injury Caused By Stroke and Traumamentioning
confidence: 99%